1994
DOI: 10.3181/00379727-207-43817
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Bifidobacterium Iongum Cultures on the Azoxymethane-Induced Aberrant Crypt Foci Formation and Fecal Bacterial  -Glucuronidase

Abstract: Epidemiologic and experimental studies suggest that consumption of fermented milk products and lactic bacterial cultures that are used to ferment the dairy products, decrease the incidence of certain types of cancer. The present study was designed to determine the effect of lyophilized cultures of Bifidobacterium longum (B. longum), a lactic bacteria, on the azoxymethane (AOM)-induced preneoplastic lesions such as aberrant crypt foci (ACF) formation in the colon and on fecal bacterial beta-glucuronidase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(41 citation statements)
references
References 0 publications
0
38
1
2
Order By: Relevance
“…may act against the development of aberrant crypt foci (ACF) in the colon of rats (Abdelali et al, 1995;Kulkarni & Reddy, 1994). Studies in vitro have shown that lactic acid bacteria have a capacity to absorb mutagens from cooked foods (Zhang & Ohta, 1993).…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…may act against the development of aberrant crypt foci (ACF) in the colon of rats (Abdelali et al, 1995;Kulkarni & Reddy, 1994). Studies in vitro have shown that lactic acid bacteria have a capacity to absorb mutagens from cooked foods (Zhang & Ohta, 1993).…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…These bacteria have been shown to possess antimutagenic and anticarcinogenic properties and data from epidemio-logical and experimental studies clearly indicate that ingestion of lactobacilli and bifidobacteria, or their fermented dairy products, reduce the risk of certain types of cancer and inhibit tumor growth (64,65). The postulated mechanisms involve alterations of luminal ph in the gut, production of antimicrobial compounds, competition for pathogen binding and receptor sites, competition for available nutrients and growth factors, stimulation of immunomodulatory cells, and production of lactase (66).…”
Section: Influence Of Nutritional Factors On Polyamine Metabolism Formentioning
confidence: 99%
“…Действие бифидобактерий на иммунную систему хорошо доказано. Оно состоит в увеличении продукции IgA [60], противоопухолевой активности [61], повышении интенсивности фагоцитоза [62], измене-нии цитокинового профиля [63], повышении активности естественных киллеров [6], активации созревания ден-дритных клеток с повышением содержания цитокинов ИЛ 10 и 12 [64], увеличении интенсивности синтеза интерферона ␣ [62], поляризации баланса T х1 /T х2 в сто-рону T х2 [23]. Одним из наиболее изученных видов бифидобактерий с пробиотическим эффектом является Bifidobacterium animalis lactis.…”
Section: обзор литературыunclassified